2009
DOI: 10.1186/1471-2202-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and neurochemical features of cholinergic neurons in the murine cerebral cortex

Abstract: Background: The existence and role of intrinsic cholinergic cells in the cerebral cortex is controversial, because of their variable localization and morphology in different mammalian species. We have applied choline acetyltransferase (ChAT) immunocytochemistry to study the distribution of cholinergic neurons in the murine cerebral cortex, in the adult and during postnatal development. For more precise neurochemical identification of these neurons, the possible colocalization of ChAT with different markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…The cortex of the Goettingen miniature pig displayed numerous ChAT-ir fibers similar to other mammals (e.g., humans, Mufson et al, 1989; Mesulam et al, 1992; nonhuman primates, Mrzljak and Goldman-Rakic, 1993; Mesulam, 2004; Raghanti et al, 2008; rodents, Ichikawa and Hirata, 1986; Lysakowski et al, 1986; Mechawar et al, 2000). Small ChAT positive neurons were seen within the cingulate, insular and piriform cortices as described in some rodent species (Eckenstein and Baughman, 1984; Mufson and Cunningham, 1988; Mechawar et al, 2000; Bhagwandin et al, 2006; Consonni et al, 2009) including murid rodents (Kruger et al, 2012) and the Hottentot golden mole (Calvey et al, 2013), but not in the BALB/c ByJ mouse (Kitt et al, 1994), guinea pig (Maley et al, 1988), monotremes (Manger et al, 2002) and most nonhuman primates (Mesulam et al, 1984; Everitt et al, 1988; Kordower et al, 1989). ChAT positive neurons in supragranular cortical layers (II–IV) have been reported in some rodent species (Eckenstein and Baughman, 1984; Mufson and Cunningham, 1988; Mechawar et al, 2000; Bhagwandin et al, 2006; Consonni et al, 2009), rabbit (Varga et al, 2003), feline (Avendaño et al., 1996), fetal Macaca mulatta (Hendry et al, 1987) and to a lesser degree in humans (Kasashima et al, 1999).…”
Section: Discussionmentioning
confidence: 81%
“…The cortex of the Goettingen miniature pig displayed numerous ChAT-ir fibers similar to other mammals (e.g., humans, Mufson et al, 1989; Mesulam et al, 1992; nonhuman primates, Mrzljak and Goldman-Rakic, 1993; Mesulam, 2004; Raghanti et al, 2008; rodents, Ichikawa and Hirata, 1986; Lysakowski et al, 1986; Mechawar et al, 2000). Small ChAT positive neurons were seen within the cingulate, insular and piriform cortices as described in some rodent species (Eckenstein and Baughman, 1984; Mufson and Cunningham, 1988; Mechawar et al, 2000; Bhagwandin et al, 2006; Consonni et al, 2009) including murid rodents (Kruger et al, 2012) and the Hottentot golden mole (Calvey et al, 2013), but not in the BALB/c ByJ mouse (Kitt et al, 1994), guinea pig (Maley et al, 1988), monotremes (Manger et al, 2002) and most nonhuman primates (Mesulam et al, 1984; Everitt et al, 1988; Kordower et al, 1989). ChAT positive neurons in supragranular cortical layers (II–IV) have been reported in some rodent species (Eckenstein and Baughman, 1984; Mufson and Cunningham, 1988; Mechawar et al, 2000; Bhagwandin et al, 2006; Consonni et al, 2009), rabbit (Varga et al, 2003), feline (Avendaño et al., 1996), fetal Macaca mulatta (Hendry et al, 1987) and to a lesser degree in humans (Kasashima et al, 1999).…”
Section: Discussionmentioning
confidence: 81%
“…With the exception of the lizard Gallotia (Medina et al 1993), no ChAT-ir cells have been found in the cortex of birds and reptiles Brauth et al 1985;Hoogland and Vermeulen-Van der Zee 1990;Powers and Reiner 1993;Medina and Reiner 1994). In mammals, cholinergic cells have been detected in the cortex of rats (Houser et al 1983;Ichikawa and Hirata 1986;Parnavelas et al 1986;Ichikawa et al 1997) and mice (Mufson and Cunningham 1988;Consonni et al 2009) but not dogs, cats, guinea pigs, other rodents, monotremes (Kimura et al 1981;Vincent and Reiner 1987;Maley et al 1988;St-Jacques et al 1996;Manger et al 2002;Bhagwandin et al 2006) or adult primates including humans Satoh and Fibiger 1985;Mesulam and Geula 1988;Geula et al 1993;Alonso and Amaral 1995). Therefore, the presence of cholinergic cells in the pallium/cortex of vertebrates is is most likely not a primitive feature for vertebrates.…”
Section: Localization Of Chat-ir Elements In the Forebrain Of Lungfismentioning
confidence: 93%
“…Studies of birds and reptiles have revealed the lack of cholinergic cells in cortical regions Brauth et al, 1985;Hoogland and Vermeulen-Van der Zee, 1990;Powers and Reiner, 1993;Medina and Reiner, 1994], with the lone exception of the lizard Gallotia gallotia [Medina et al, 1993]. In mammals, cholinergic cells were detected in the cortex of rats [Houser et al, 1985;Ichikawa and Hirata, 1986;Parnavelas et al, 1986;Ichikawa et al, 1997] and mice [Mufson and Cunningham, 1988;Consonni et al, 2009] but not in dogs, cats, guinea pigs, some rodents, monotremes [Kimura et al, 1981;Vincent and Reiner, 1987;Maley et al, 1988;St-Jacques et al, 1996;Manger et al, 2002;Bhagwandin et al, 2006] and adult primates, including humans Satoh and Fibiger, 1985;Mesulam and Geula, 1988;Geula et al, 1993;Alonso and Amaral, 1995]. Therefore, the presence of cholinergic cells in the pallium/cortex of vertebrates seems to be a variable feature that appears several times in evolution.…”
Section: Localization Of Chat-ir Elements In the Forebrain Of Holosteansmentioning
confidence: 99%